2023
DOI: 10.1186/s13046-023-02767-1
|View full text |Cite
|
Sign up to set email alerts
|

FBXW7 in breast cancer: mechanism of action and therapeutic potential

Siyu Chen,
Ping Leng,
Jinlin Guo
et al.

Abstract: Breast cancer is one of the frequent tumors that seriously endanger the physical and mental well-being in women. F-box and WD repeat domain-containing 7 (FBXW7) is a neoplastic repressor. Serving as a substrate recognition element for ubiquitin ligase, FBXW7 participates in the ubiquitin–proteasome system and is typically in charge of the ubiquitination and destruction of crucial oncogenic proteins, further performing a paramount role in cell differentiation, apoptosis and metabolic processes. Low levels of FB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…Noteworthy, the growing evidence of the therapeutic approaches is proposed in terms of the treatment for MYCN-associated tumors, which targets MYCN transcription, stability, MYCN cofactors/ coregulators and MYCN downstream targets (121). In addition, the investigations targeting hedgehog signaling, cyclin D, and FBXW7 are also under development (122)(123)(124)(125). Though its relative difficulty for application to developmental disease due to the more intricate adjustment during development, not only quantitatively but also geographically, this oncologic knowledge might contribute to the development of therapeutic approaches even to the developmental disorders discussed in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, the growing evidence of the therapeutic approaches is proposed in terms of the treatment for MYCN-associated tumors, which targets MYCN transcription, stability, MYCN cofactors/ coregulators and MYCN downstream targets (121). In addition, the investigations targeting hedgehog signaling, cyclin D, and FBXW7 are also under development (122)(123)(124)(125). Though its relative difficulty for application to developmental disease due to the more intricate adjustment during development, not only quantitatively but also geographically, this oncologic knowledge might contribute to the development of therapeutic approaches even to the developmental disorders discussed in this review.…”
Section: Discussionmentioning
confidence: 99%
“…FBXW7 primarily targets oncoproteins for degradation and is thus widely recognized as a classic tumor suppressor gene. Previous studies on breast cancer have shown that the mutation frequency of FBXW7 in TNBC is considerably higher than that in ER receptor-positive BC [ 19 ]. It has also been observed that FBXW7 plays a role in ubiquitinating and degrading EglN2, thereby inhibiting TNBC tumorigenesis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…FBXW7 also inhibits the MITF/PGC-1α pathway, thereby suppressing melanoma cell proliferation relying on mitochondrial oxidative metabolism [43]. Downregulation of FBXW7 has been observed in breast, gastric and pancreatic cancers, where its low expression associates with unfavorable prognosis [44][45][46]. As in melanoma, FBXW7 exhibits anti-tumor activities in other cancers by regulating oncogenes such as c-Myc and p53 [47,48].…”
Section: Discussionmentioning
confidence: 99%